Alih Fungsi Lahan di sekitar Cagar Alam lamedai dan Implikasinya Terhadap Risiko Banjir - R. Muliadi; La Sahibudin; Sahrul Sahrul (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Land-use change in the vicinity of Lamedai Nature Reserve, Kolaka Regency, has generated significant ecological pressure on the conservation area and its surrounding environment. This study aims to examine the impact of land conversion on increasing flood risk, with a particular focus on changes in land use patterns, vegetation degradation, and hydrological dynamics. The research employed a descriptive-analytical approach through the collection of primary data obtained from field observations. In addition, a systematic review method was used to evaluate and synthesize existing literature concerning the impacts of land-use change, while secondary data were collected from land cover maps, rainfall records, and flood occurrence reports. The findings indicate that land conversion, particularly for mining and plantation activities, has reduced the forest's capacity to absorb rainfall, increased soil erosion, and intensified surface runoff. These conditions have directly contributed to the rising frequency and severity of flooding in areas surrounding the nature reserve. The resulting socio-economic impacts include material losses, disruptions to community activities, and threats to the sustainability of the Lamedai Nature Reserve ecosystem. This study highlights the importance of implementing sustainable land management policies, rehabilitating degraded areas, and strengthening oversight of economic activities around conservation zones to mitigate flood disaster risks.